2018
DOI: 10.25130/tjps.23.2018.009
|View full text |Cite
|
Sign up to set email alerts
|

Fabrics dying with Hibiscus sabdariffa and Curcuma longa extracts using different mordants and mordanting methods

Abstract: Extraction of plant secondary metabolites were prepared and subjected as non-toxic, biodegradable and eco-friendly natural dyes. Two groups of cotton textiles were dyed with crude extracts of Curcuma longa and Hibiscus sabdariffa separately to examine and compare the staining ability of these extracts. Fabrics where treated with three different mordanting techniques using three different mordants which were copper, ferrous sulfates and potassium dichromate. Dyed fabrics were exposed to different conditions inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The a * – b * plot revealed (Figure 2) that the cotton fabrics dyed with pine cone, copper, and tannic acid were slightly inclined toward the yellow coordinate of the yellow‐red zone, while other mordants were more toward the blue coordinate of the blue‐red zone. This was consistent with other studies, showing that the complex formation of anthocyanins with metal salts could lead to a blue colour 28,29,39 …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The a * – b * plot revealed (Figure 2) that the cotton fabrics dyed with pine cone, copper, and tannic acid were slightly inclined toward the yellow coordinate of the yellow‐red zone, while other mordants were more toward the blue coordinate of the blue‐red zone. This was consistent with other studies, showing that the complex formation of anthocyanins with metal salts could lead to a blue colour 28,29,39 …”
Section: Resultssupporting
confidence: 93%
“…Figure 5 shows that the meta‐mordanting procedure had the highest K / S value among the three mordanting methods for both metal mordants and bio‐mordants. Researchers, in the dyeing of cotton with the H. sabdariffa extract and in the presence of metal salts, also found that the pre‐mordanting method led to a lighter shade than the other two methods; 39 therefore, it is not the desired method to produce good colour strength 40 . Since the colour fastness of H. sabdariffa on the fibre is low, in the after‐mordanting method, part of the anthocyanins transfer from the cotton fabric to the mordant bath, and the colour strength ( K / S ) was decreased.…”
Section: Resultsmentioning
confidence: 99%